Integrating Risk Management with Strategic Planning: A Case Study of the Libyan Academy for Postgraduate Studies' Strategic Plan (Sebha University Conference Proceedings, 2025)
Strategic planning helps define the future vision and long-term goals of the organization, while the risk plan represents protection for these goals from unexpected surprises and challenges. The more organizations are prepared to explore and identify risks in advance, the greater their chances of success in achieving their goals. These plans must be logically integrated so that the strategy includes effective mechanisms for monitoring and managing risks. Leveraging knowledge and experience from strategic plans and risk plans enhances decision-making and supports corporate governance. Therefore, developing a culture that integrates the use of these tools enhances the ability to innovate and adapt, leading to competitive advantage and the continuity of the organization in the market. Despite the abundance of studies on strategic planning, the scientific literature lacks research that addresses risk management to achieve strategic goals. This study highlights the importance of risk management using ISO 31000:2018 guidelines in strategic planning and its application to strategic plans, based on a clear vision and understanding of the comprehensive application of risk management, governance, and compliance. The main objective of this study is to analyze the risks that hinder the achievement of strategic goals. That is, identifying potential risks and evaluating them quantitatively and qualitatively. The seven objectives were analyzed through similar studies and brainstorming, in addition to expert consultations, taking into account the internal and external environment of the academy. Scenarios and assumptions were developed to extract evidence and indicators about these risks to facilitate their assessment and clarify them specifically as high, medium, and low risks, with the aim of transforming them into responsibilities and priorities that can be implemented through questionnaires distributed to a sample of stakeholders. These steps resulted in identifying 106 risks, including 18 risks for the first objective, 24 risks for the second objective, 11 risks for the third objective, 10 risks for the fourth objective, 15 risks for the fifth objective, 8 risks for the sixth objective, and 6 risks for the seventh objective. In addition, the researchers considered that there is a group of risks common to all objectives related to planning and administrative organization, which in turn contributed to enhancing the achievement of the objectives, and they were independently allocated at a rate of 16 risks. In total, 22% of the expected risks are high, 70% are medium, and 8% are low. Goal 7 topped the list of high risks, followed by Goal 5. Goal 2, the sixth, had the lowest percentage of high risks. The percentage of medium risks was the largest in Goal 4, followed by Goal 6, then Goal 2, then Goal 3. The highest percentage of low risks was in Goal 2, followed by Goal 6, then Goal 4, then Goal 5. The results showed that risk management plays an important role in integrating operational departments and enhancing strategic leadership, as it links systems such as governance and internal control into one system that supports strategic planning according to ISO 31000:2018. It is necessary to integrate it into academic culture and daily activities to ensure effective institutional performance and to integrate mechanisms for confronting threats and assessing risks.